A comparative clinical and echocardiography study of acute myocardial infarction, patients above and below 40 years of age - Dr. Nayan Kumar Patel; Dr. Gouri Oram; Dr. Prafulla Kumar Bariha (International Journal of Medical Research and Review, 2020)
ABSTRACT BACKGROUNDMyocardial infarction is one of the major health problems in both developed and developing countries and is the leading cause of premature death among adults in developed countries while its incidence is on an increase in developing countries as well, including India. Coronary Artery Disease (CAD) in young (<40 years) has aroused considerable interest in recent years.OBJECTIVES. To determine the prevalence of various risk factors in young AMI patients and to compare them with that of older patients. To compare the clinical presentation, course and complications among both the groups.METHODS:Clinical Criteria : Severe excruciating retrosternal pain with or without radiation to upper extremities, abdomen, back, neck or jaw, not relieved by rest, lasting more than 30 minutes and frequently for a number of hours suggested the diagnosis of MI. Where the pain was not a prominent feature other features like severe diaphoresis, syncope, shock, sudden dyspnoea, and sudden onset of pulmonary oedema in the absence of other known cause of acute left ventricular failure were taken into consideration. When any of these features including a prolonged retrosternal pain especially in a person with known coronary risk factors were present the possibility of acute MI was strongly suspected and further laboratory investigations were done to settle the diagnosis.RESULTS & DISCUSSIONAMI was found to have male preponderance with M:F ratio of 9:1 and 2:8:1 in group I & II patients respectively. Smoking habit was found to be the commonest risk factors. Equal patients in each group had TC/HDL-C ratio in excess of 4.5.Anterior wall infarction was the commonest form of infraction in both Groups. Among the early complications, the occurrence of heart failure was found to be significantly high in Group II patients. Other complications such as arrhythmias, & conduction defects, shock, pericarditis, post infarction angina, thromboembolic episodes & mitral regurgitation did not differ significantly in incidence when both groups were compared. Heart failure occurred in significantly higher percentage in group II patients than in Group I patients.  Anterior apical, septal, anterolateral, inferior, basal & posterior, wall motion abnormalities were found in both groups. Death was more in Group II patients during early hospitalization period.CONCLUSION:In the present study it is clearly evident that the natural course, extent of ventricular dysfunction arrythmias / wall motion abnormalities/ mortality in acute myocardial infarction bears many similarity in both younger and older patient population; but not in all aspects. Family history of coronary heart disease and obesity may be more associated with younger and older patient groups respectively while incidence of heart failure in older patients are significantly higher when compared with that is seen in younger patients. Key words: Coronary Artery Disease (CAD), Young AMI, Echocardiography in AMI